Lecciones únicas e hipotexto del Catón en romance de Gonzalo García de Santa María: el incunable poético 93*CA. - MARINI, MASSIMO (Scripta, 2024)
The aim of this paper is to study a selection of Spanish poetic glosses that Gonzalo García de Santa María made on the Disticha Catonis, published in Zaragoza around 1493, by Pablo Hurus (93*CA). Following the method of the underlying collatio, the action that the Latin hypotext could have exerted on the Castilian text will be demonstrated, in order to study the textual relations established between the model and its gloss both at a synchronic level, in the hermeneutic operation carried out by the translator, and at a diachronic level, in the complex stratification that the history of the transmission of the Disticha implies. Critical reflection will address both the monostic section of the work and the distichs themselves.